Effects of transcutaneous auricular vagus nerve stimulation (tVNS) on balance in patient with chronic lower back pain - Meisy Andriana; Dewi Poerwandari; Damayanti Tinduh; Paulus Sugianto; Soenarnatalina Melaniani (Romanian Journal of Neurology)
Background. tVNS is a technique of electrical stimulation of vagus nerve afferents that is used as a therapy for chronic pain. This study aims to analyze the effect of adding tVNS to exercise therapy on dynamic balance in chronic LBP patients measured by Maximized Reach Distance (%MAXD) and composite score of Modified Star Excursion Balance Test (MSEBT). Method. The method is an experimental study with a pretest-posttest randomized control group study. 22 people with mechanical chronic LBP aged 16-55 years who were randomly allocated into an exercise group (control group) and an exercise plus tVNS group (intervention group). MSEBT dynamic balance was measured before and after intervention. Results. In the intervention group the average MSEBT anterior right and left leg before (74.57±14.72;73.53±15.0) after (86.45±15.98; 86.98±15.9), posteromedial right and left before (88.23±16.76; 75.15±15.04) after (99.65±14.56, 92.19±11.91), right and left posterolateral before (76.66±13.89, 78.02±13.44) after (84.00±17.25, 84.30±13.90) there was a significant difference (p <0.05). Comparing anterior ∆MSEBT, right composite score and left posteromedial posterolateral ∆MSEBT between groups, there was a significant difference (p <0.05), not significant in right posteromedial posterolateral ∆MSEBT. Conclusion. The addition of tVNS to exercise therapy after 2 weeks on dynamic balance with MSEBT assessment showed a significant improvement in the intervention group. The results were better in the intervention group than in the control group. Further research is still needed to investigate the potential of adding tVNS to chronic LBP.